Locating initial breakdown pulses using electric field change network. Issue 13 (1st July 2013) - Karunarathne, Sumedhe; Marshall, Thomas C.; Stolzenburg, Maribeth; Karunarathna, Nadeeka; Vickers, Lauren E.; Warner, Tom A.; Orville, Richard E.
Abstract : [1] Initial breakdown pulses (IBPs) observed in the fast electric field change (E‐change) at the beginning of intracloud (IC) and cloud‐to‐ground (CG) lightning flashes are located using a time‐of‐arrival technique called Position By Fast Antenna (PBFA) with data from a network of 10 E‐change sensors located at Kennedy Space Center. Location errors, estimated using a Monte Carlo method, are usually less than 100 m for horizontal coordinates and several hundreds of meters for altitude, depending on distance to the sensors and altitude of the source. Comparison of PBFA source locations to locations from a VHF lightning mapping system (Lightning Detection and Ranging II (LDAR2)) shows that PBFA locates most of the "classic" IBPs while LDAR2 locates only a few percent of them. As the flash develops during the IB stage, PBFA and LDAR2 obtain similar locations when they detect the same IBPs. The overall vertical motion indicated by the PBFA positions of IBPs was downward with time for CG flashes and upward with time for IC flashes. Location of the fast pulses due to return strokes of CG flashes is also determined using PBFA. Comparison to locations from the Cloud‐to‐Ground Lightning Surveillance System (CGLSS) shows that PBFA reliably locates ground strokes. These results are verified using ground truth data acquired with a high‐speed video camera. After cross calibration with the CGLSS data set, peak currents of return strokes are also determined. Key Points: Obtaining locations of lightning initial breakdown pulses using E‐change network Physical length of the pulses detected Obtaining lightning locations from high‐speed video recordings